The debt crisis and the impasse of development: its implications for peace - Alcalde Cardoza, Javier (1989)
This paper contends that the conventional development model, based on intensive investment and industrialization; has run out of steam in the Third World, as a consequence of the end of a Golden Age of growth of the world economy. It outlines the impact of the debt crisis upon development and particularly its economic and social effects in Latin America, suggesting the need of a new regional development model. The article points to a gradual decay of the international development ethos, caused by a series of moral, technical, political and economic reversals of the project of universal economic progress. It highlights the implications for domestic and international peace of contemporary development problems, aggravated by the vanishing of growth.